Study of operation of a polymer insulator under uniform and non-uniform contamination - D. K. Zaripov; R. A. Nasibullin; D. F. Zakirov; A. V. Zakharov (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE. Suspended insulators, the technical condition of which largely determines the reliability of power supply to consumers of different categories, are one of the most damaged elements of overhead power transmission lines [1-2]. This is primarily due to the fact that during their operation, insulators are exposed to various climatic conditions that have a direct impact on their insulating properties. Moreover, precipitation, such as rain, fog or dew, has the greatest impact precisely in combination with various solid, liquid and gaseous particles deposited on the insulator surface from the air, and forming a layer of surface contamination. Wetting this layer increases the electrical conductivity of the entire overhead line insulation structure and reduces its insulating capacity. Study of influence of dampening of contaminated surface of suspended insulation on their discharge characteristics is an urgent scientific task. The solution of this task enables to develop the existing understanding of the mechanisms of formation and development of discharges on the contaminated and wetted surface of insulation and to formulate the appropriate diagnostic attributes applicable to control the condition of the overhead power line insulators. OBJECTIVE. To carry out laboratory research aimed at studying the behavior of suspended high-voltage polymer insulators of overhead power lines when they are moistened. To formulate appropriate diagnostic attributes applicable for control of condition of suspended insulators of overhead power lines during their operation. METHODS. At the solution of the posed problem experimental methods of research, consisting in simulation of work of the contaminated polymeric insulator in the atmosphere of a pure fog with application of the special experimental installation developed by the authors of this article were applied. RESULTS. As a result of laboratory research, by continuous registration of leakage current values, as well as signals coming from the remote sensor, characteristic features of contaminated insulator humidification were revealed, which can be used as diagnostic signs in the process of their operation.